2019
DOI: 10.1186/s13058-019-1162-8
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of circulating insulin-like growth factor-I and binding proteins 1–7 with mammographic density among women undergoing image-guided diagnostic breast biopsy

Abstract: Background Mammographic density (MD) is a strong breast cancer risk factor that reflects fibroglandular and adipose tissue composition, but its biologic underpinnings are poorly understood. Insulin-like growth factor binding proteins (IGFBPs) are markers that may be associated with MD given their hypothesized role in breast carcinogenesis. IGFBPs sequester IGF-I, limiting its bioavailability. Prior studies have found positive associations between circulating IGF-I and the IGF-I:IGFBP-3 ratio and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…With regard to the association between mammographic density and serum IGF-1, there are controversial findings: Diorio et al (2005) found a positive association in premenopausal women, but other studies did not support this result ( Rice et al, 2012 ; Rinaldi et al, 2014 ). Recently, Hada et al (2019) demonstrated a positive association between circulating IGFBP2 and mammographic density particularly among women with lower BMI, but no strong correlation with IGF-1.…”
Section: Plasma Levels Of Igf-1 and Breast Cancermentioning
confidence: 99%
“…With regard to the association between mammographic density and serum IGF-1, there are controversial findings: Diorio et al (2005) found a positive association in premenopausal women, but other studies did not support this result ( Rice et al, 2012 ; Rinaldi et al, 2014 ). Recently, Hada et al (2019) demonstrated a positive association between circulating IGFBP2 and mammographic density particularly among women with lower BMI, but no strong correlation with IGF-1.…”
Section: Plasma Levels Of Igf-1 and Breast Cancermentioning
confidence: 99%
“…The oncogenic activity of IGFBP2 can be explained by its IGFindependent activities: it possesses a functional integrin-binding domain, heparin binding domains and a nuclear localization signal motif as well, all contributing to cellular signaling leading to cell proliferation, migration, and angiogenesis (23). In case of benign proliferative breast diseases and various type of breast cancers, the level of IGFBP2 both in serum and tumor mass may be upregulated (24,25), moreover, IGFBP2 has proliferative effect on breast cancer cell lines (26) and it is associated with the endocrine resistance of breast cancer (27), which suggests that IGFBP2 is oncogenic and it is a potential biomarker (16). Based on IGFBP2 positivity of breast cancers, a DNA vaccine was designed, encoding HER-2/neu, IGFBP2 and insulin-like growth factor 1 receptor (IGF1R) as tumor associated antigens and it proved to be effective in preclinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48] The role of IGFBPs has been studied intensely for its association with breast cancer. [49][50][51] Contradictory to the widely reported role of IGFBPs, Probst-Hensch et al found that circulating IGFBP2 and 3 were profoundly expressed in breast cancers and may have a dependence on body weight and hormonal effect. 49 McCarthy et al found that there was a positive correlation between IGFBP3 and IGF-1 mRNAs in breast cancer cells and this association was not found in normal breast cells.…”
Section: Igf Binding Proteins (Igfbps)mentioning
confidence: 99%